Assessing the Effectiveness of Youth Training Programmes in Non-Violent Response: A Case Study of Tamale Metropolis, Ghana - Nahyi, James Abdallah; Titigah, Gregory; Sanka, Mohammed (Advances in Social Sciences Research Journal, 2025)
While the contributions of governments and Civil Society Organizations in peacebuilding in the Northern Region of Ghana is well documented, the influence of training on non-violent response to conflicts is not clearly established. This study evaluates the use of training programmes as a strategy to prevent violent conflicts. It contributes to the theoretical understanding of violent conflicts, while teasing out the reasons why it persists. This paper is based on the Human Needs theory that seeks to rationalise the linkage between human needs and violent conflicts. This research used a mixed-methods approach, collecting qualitative and quantitative data through interviews, document reviews, and questionnaires from officials from the Christian Council of Ghana and youth from in five communities. The study concludes that the training on non-violence for the youth contributes but cannot exclusively ensure non-violent response to conflicts. The study notes that some unemployed youth are lured into violent conflicts for economic benefits. The study recommends factoring livelihood schemes into conflict management programmes. Train the youth with employable skills and create job opportunities for them. It also recommends integration of peace building programmes into educational and religious based institutions.